Sample preparation method of iron and steel continuous casting billet oxide scale for electron microscope analysis

Through the steps of silver glue treatment, cold inlay, grinding and gold spray coating conductive treatment, the problem of iron oxide sheet of steel continuous casting billets is solved, ensuring its integrity and stability, and providing electron microscope analysis Reliable and accurate samples.

CN119470514APending Publication Date: 2025-02-18BEIJING SHOUGANG CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411566667.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The iron oxide sheet of steel continuous casting billet is fragile during the sample preparation process, causing it to fall off during the sample grinding process, affecting the integrity of the iron oxide sheet and the accuracy of data analysis.

Method used

The steps of silver glue treatment, cold inlay, grinding and polishing, gold spray coating conductive treatment are adopted to ensure the integrity and stability of the iron oxide sheet, so that it can maintain its original state in electron microscopy analysis.

Benefits of technology

Through fine sample preparation steps, the integrity and stability of the iron oxide sheet are ensured, and clear component detection is achieved, providing a more reliable and accurate sample basis for electron microscopy analysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470514A_ABST
    Figure CN119470514A_ABST
Patent Text Reader

Abstract

The invention relates to a sample preparation method of steel continuous casting billet oxide scale for electron microscope analysis, and belongs to the technical field of steel material physical analysis. The method comprises the following steps: carrying out elargol treatment on a steel sample containing scale easy to fall off; carrying out cold inlaying on the test sample subjected to silver colloid treatment by using cold inlaying liquid, and then drying the test sample; carrying out grinding and polishing treatment on the dried sample; performing metal spraying, film coating and electric conduction treatment on the sample subjected to the grinding and polishing treatment; adhering the bottom surface of the sample subjected to the metal spraying and coating conductive treatment to a sample table, and then connecting the detection surface of the sample with the sample table, so that the sample and the sample table form a whole sample; and blowing and wiping the whole sample by using compressed air. According to the method, through a series of optimization treatment steps, the preparation quality of the iron and steel continuous casting billet oxide scale sample is remarkably improved, and a more reliable and accurate sample basis is provided for electron microscope analysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of physical analysis of steel materials, and in particular to a method for preparing samples of iron oxide scale of steel continuous casting billets for electron microscope analysis. Background Art

[0002] High-temperature oxidation of steel materials is an inherent property of the material. The structure, thickness and density of the iron oxide scale change with different thermal processing processes. The molten steel undergoes a long high-temperature oxidation process from the crystallizer to the heating furnace and then to the finished plate and strip. Therefore, there are differences in the structure and thickness of the iron oxide scale. Therefore, the iron scale exhibits characteristics of good adhesion or fragility under the action of external forces.

[0003] In order to obtain better surface quality of finished plates and strips, the research on the complete oxide scale structure has never stopped. However, in the actual processing and sampling process, there are often great difficulties in the processing and sampling and grinding and polishing of fragile oxide scale. Different from the characteristics of small thickness and high adhesion of hot-rolled oxide scale, the cast iron scale has the characteristics of loose and fragile texture. It is very easy to fall off during the sample grinding process, which affects the integrity of the oxide scale and cannot effectively guarantee the original state of the sample oxide scale. It affects the accuracy of the data analysis of cast oxide scale and further affects the effective development of process research. Based on the research needs of the complete oxide scale structure of continuous casting billets, combined with the multi-layer and fragile characteristics of the oxide scale of continuous casting billets, it is necessary to develop a proprietary processing and sampling method to solve the problem of the integrity of the oxide scale sampling process. Summary of the invention

[0004] The present application provides a method for preparing a sample of iron oxide scale of a steel continuous casting billet for electron microscope analysis, so as to solve the following technical problem: how to improve the integrity of the iron oxide scale of the continuous casting billet during the sample preparation process.

[0005] The present application provides a method for preparing a sample of iron oxide scale of a steel continuous casting billet for electron microscope analysis, the method comprising:

[0006] The steel samples containing easily detached iron oxide scale were treated with silver glue;

[0007] Using a cold mounting solution, cold mounting the sample after the silver glue treatment, and then drying the sample;

[0008] Performing grinding and polishing treatment on the dried sample;

[0009] Conductive treatment of gold spraying and plating is performed on the sample after grinding and polishing;

[0010] Adhere the bottom surface of the sample after the gold-sprayed conductive treatment to the sample stage, and then connect the detection surface of the sample to the sample stage, so that the sample and the sample stage become a whole sample;

[0011] The entire sample was blown clean with compressed air.

[0012] Optionally, the thickness of the silver paste is 1 mm to 2 mm.

[0013] Optionally, the cold mounting solution comprises epoxy resin and a curing agent.

[0014] Optionally, the mass ratio of the epoxy resin to the curing agent is 1:(1.8-2.1).

[0015] Optionally, the drying is performed under a vacuum state.

[0016] Optionally, the drying temperature is 30° C. to 40° C., and the drying time is ≥12 h.

[0017] Optionally, the grinding and polishing process is a multi-pass polishing process, wherein each polishing process lasts for 15S to 30S.

[0018] Optionally, in the interval between two adjacent polishing passes of the multi-pass polishing, the polished surface of the sample is subjected to a first air cooling, and the time of the first air cooling is 8S to 10S.

[0019] Optionally, after the grinding and polishing treatment and before the gold spraying and conductive treatment, the sample is subjected to a second air cooling, and the time of the second air cooling is 5 minutes to 8 minutes.

[0020] Optionally, the coating current of the gold-spraying conductive coating treatment is 18 mA to 20 mA, and the coating time of the gold-spraying conductive coating treatment is 130S to 150S.

[0021] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0022] The present application provides a method for preparing samples of iron oxide scale of steel continuous casting billets for electron microscope analysis, the method comprising: treating a steel sample containing easily detached iron oxide scale with silver glue; using a cold embedding liquid to cold embed the sample after the silver glue treatment, and then drying the sample; grinding and polishing the dried sample; spraying gold coating and conducting the sample after the grinding and polishing treatment; adhering the bottom surface of the sample after the gold coating and conducting treatment to a sample stage, and then connecting the detection surface of the sample to the sample stage so that the sample and the sample stage become a sample as a whole; using compressed air to blow and wipe the sample as a whole. The method can ensure the integrity and stability of the iron oxide scale through fine sample preparation steps, including silver glue reinforcement, cold embedding, grinding and polishing, gold coating, etc., so that the original state of the iron oxide scale of the steel continuous casting billet can be fully and comprehensively displayed, and clear component detection can be achieved, providing a more reliable and accurate sample basis for electron microscope analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0025] Figure 1 A schematic flow chart of a method for preparing a sample of iron scale of a steel continuous casting billet for electron microscope analysis provided in an embodiment of the present application;

[0026] Figure 2 The energy spectrum component analysis results of the interface between the iron oxide scale and the substrate provided in the embodiments of the present application. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0028] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0029] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0030] Figure 1 A schematic flow chart of a method for preparing a sample of iron scale of a steel continuous casting billet for electron microscope analysis provided in an embodiment of the present application;

[0031] like Figure 1 As shown, the embodiment of the present application provides a method for preparing a sample of iron oxide scale of a steel continuous casting billet for electron microscope analysis, comprising:

[0032] S1. Silver glue treatment is performed on steel samples containing easily detached iron oxide scale;

[0033] Select representative areas from the steel continuous casting ingot as samples, and avoid selecting defective or heavily contaminated parts. Before preparing the sample, you can use an organic solvent such as anhydrous ethanol or acetone to gently wipe the sample surface to remove impurities such as oil, dust, etc. on the surface to reduce the impact of external factors on the integrity of the oxide scale.

[0034] In some embodiments, the thickness of the silver paste is 1 mm to 2 mm.

[0035] The positive effect of limiting the thickness of silver glue to 1mm to 2mm: Silver glue can not only effectively enhance the bonding strength between the sample and the subsequent embedding material, preventing the sample from falling off or being damaged during the subsequent processing, but also provide a certain degree of conductivity for the sample. In particular, limiting the thickness of silver glue to 1mm to 2mm, this thickness range can not only ensure sufficient bonding strength, but also avoid the processing difficulties and cost increase caused by excessive thickness, which is one of the key steps to achieve efficient sample preparation.

[0036] S2, using a cold mounting solution to cold mount the sample after the silver glue treatment, and then drying the sample;

[0037] The main purpose of cold mounting is to stabilize the sample so that it is not easily damaged or detached during subsequent processing. It is also conducive to the observation and analysis of the microstructure of the material under an electron microscope. The cold mounting method can keep the original microstructure of the sample from being affected by high temperature, while enhancing the overall stability and operability of the sample.

[0038] In some embodiments, the cold mounting solution comprises epoxy resin and curing agent, and the mass ratio of the epoxy resin to the curing agent is 1:(1.8-2.1).

[0039] The positive effect of limiting the mass ratio of the epoxy resin to the curing agent to 1: (1.8-2.1): As the main component of the cold embedding liquid, epoxy resin has good adhesion and mechanical strength. When it is mixed with an appropriate amount of curing agent, it can form a strong and non-deformable embedding body, effectively protecting the sample from being damaged or deformed in subsequent processing. The mass ratio of 1: (1.8-2.1) ensures that the embedding body is neither too hard and brittle nor too soft, thereby ensuring stability while facilitating subsequent grinding and cleaning. In addition, when the ratio of epoxy resin to curing agent is within the range of 1: (1.8-2.1), it can ensure that the curing process is completed within a reasonable time, while avoiding the reduction in efficiency caused by too long curing time or the substandard quality of the embedding body caused by too short curing time. Exemplarily, the mass ratio of the epoxy resin to the curing agent can be 1: 1.8, 1: 1.9, 1: 2.0, 1: 2.1, etc.

[0040] The cold mounted specimens are solidified by drying. During the drying process, the specimens should be protected from overheating or overcooling to avoid affecting their performance and structure. The dried specimens should be promptly processed to avoid long-term exposure to air, which may lead to oxidation or contamination.

[0041] In some embodiments, the drying is performed under a vacuum state.

[0042] Drying under vacuum can significantly reduce the gas content in the cold mounting liquid, because the vacuum environment can remove dissolved gases and volatile impurities in the liquid. In this way, when the epoxy resin and curing agent are mixed and cured, no bubbles or defects will be formed due to gas escape, thus ensuring the quality and density of the inlay. In addition, the vacuum state also helps to accelerate the curing reaction. In an ordinary atmospheric environment, the curing process may be slowed down by factors such as oxygen and humidity in the air. In a vacuum state, these interfering factors are greatly reduced, allowing the curing reaction to proceed faster and more evenly.

[0043] In some embodiments, the drying temperature is 30° C. to 40° C., and the drying time is ≥ 12 h.

[0044] The positive effect of limiting the drying temperature to 30°C to 40°C: The drying temperature is set between 30°C and 40°C, which is a relatively mild temperature range. Drying within this temperature range can not only ensure the smooth curing reaction of the epoxy resin and the curing agent, but also avoid thermal damage or deformation of the sample caused by temperatures above 40°C. Mild temperatures also help to reduce the rate of chemical reactions, making the curing process more uniform and stable. Therefore, the choice of this drying temperature helps to maintain the original structure and composition of the sample and improve the accuracy of subsequent electron microscopy analysis. Exemplarily, the drying temperature can be 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, etc.

[0045] The positive effect of limiting the drying time to ≥ 12h: This is to ensure that the epoxy resin and curing agent in the cold mounting solution can fully react and solidify. A drying time of ≥ 12h can make the chemical reaction inside the inlay more thorough, forming a stronger and more stable structure. In addition, a drying time of ≥ 12h can also help reduce stress concentration and residual stress inside the inlay, and reduce cracks or deformation that may occur in subsequent processing. Therefore, the selection of drying time is of great significance for improving the overall quality and stability of the sample. Exemplarily, the drying time can be 12h, 12.5h, 13h, 13.5h, 14h, etc.

[0046] S3, grinding and polishing the dried sample;

[0047] The sample is ground and polished to remove surface defects and uneven parts and improve the smoothness and finish of the observation surface. During the grinding and polishing process, the force and speed should be controlled to avoid excessive grinding that causes the oxide scale to fall off or break.

[0048] In some embodiments, the grinding and polishing process is a multi-pass polishing process, wherein each polishing process lasts for 15S to 30S.

[0049] The positive effect of limiting the polishing time of each pass to 15S to 30S is that it helps to ensure uniformity and stability during the polishing process. A polishing time of less than 15S may result in insufficient polishing, with rough scratches or unevenness on the surface; while a polishing time of more than 30S may cause over-polishing, damage the microstructure of the sample surface, and frictional heat will also cause the microbubbles in the cold mount to liquefy and contaminate the sample. Therefore, an appropriate polishing time can balance these two factors and obtain a smooth and uniform sample surface. Exemplarily, the polishing time of each pass can be 15S, 18S, 21S, 24S, 27S, 30S, etc.

[0050] In some embodiments, the bottom of the dried sample is smoothed with 200-mesh, 600-mesh, and 1000-mesh sandpapers in sequence to ensure the stability of the sample when it is placed on the sample stage.

[0051] In some embodiments, the test surface of the dried sample is ground with 200 mesh, 500 mesh, 1000 mesh and 1200 mesh sandpaper in sequence; then polished with 0.7 μm and 0.35 μm diamond polishing agents in sequence; and finally polished with deionized water to ensure that the sample surface is clean and free of dirt.

[0052] In some embodiments, in the interval between two adjacent polishing passes of the multi-pass polishing, the polished surface of the sample is subjected to a first air cooling, and the first air cooling time is 8S to 10S.

[0053] The positive effect of limiting the first air cooling time to 8S to 10S: During the polishing process, the heat generated by friction will increase the surface temperature of the sample. Air cooling the polished surface of the sample can effectively reduce the temperature of the polished surface and prevent thermal damage or changes in the surface microstructure caused by high temperature. This is crucial to maintaining the original morphology and properties of the sample. If the first air cooling time is shorter than 8S, the effect is not good, and if the first air cooling time is longer than 10S, the efficiency is low. Exemplarily, the first air cooling time can be 8S, 8.5S, 9S, 9.5S, 10S, etc.

[0054] In some embodiments, after the grinding and polishing treatment and before the gold spraying and conductive treatment, the sample is subjected to a second air cooling, and the second air cooling time is 5 minutes to 8 minutes.

[0055] The positive effect of limiting the second air cooling time to 5 minutes to 8 minutes: This process is designed to ensure that the sample test surface is dry and no moisture remains. Provide a cleaner, undisturbed sample surface for subsequent analysis, testing or storage. If the second air cooling time is less than 5 minutes, the moisture between the sample and the gap between the mounting base material cannot be completely removed; if the second air cooling time is greater than 8 minutes, the work efficiency is reduced. Exemplarily, the second air cooling time can be 5 minutes, 5.5 minutes, 6 minutes, 6.5 minutes, 7 minutes, 7.5 minutes, 8 minutes, etc.

[0056] S4, performing a gold-spraying and conductive treatment on the sample after the grinding and polishing treatment;

[0057] The sample is subjected to gold-sprayed conductive treatment to enhance the conductivity of the sample and ensure clear images and accurate data during electron microscope observation. The conductive treatment of the gold-sprayed coating should be uniform and consistent to avoid local over-thickness or over-thinness, which will affect the observation effect. The thickness of the gold-sprayed coating needs to be carefully selected. If the coating thickness is too large, part of the morphology and composition contrast may be lost; if the coating thickness is too small, the signal enhancement is limited.

[0058] In some embodiments, the coating current of the gold-spraying conductive coating treatment is 18 mA to 20 mA, and the coating time of the gold-spraying conductive coating treatment is 130S to 150S.

[0059] The coating current directly affects the thickness and uniformity of the gold film. In the range of 18mA to 20mA, the current is strong enough to ensure that gold atoms can be evenly deposited on the surface of the sample to form a continuous and dense metal film. This high-quality metal film can not only significantly improve the conductivity of the sample, but also help to enhance the imaging effect of the sample under the electron microscope, making the observed image clearer and more delicate. In addition, gold spraying within an appropriate current range can ensure that the coating process is neither too fast nor too slow. A coating speed faster than 20mA may cause uneven thickness of the gold film or defects such as pores; while a too slow coating speed will reduce the efficiency of sample preparation. Therefore, the current range of 18mA to 20mA is the key to achieving efficient coating. Exemplarily, the coating current can be 18mA, 18.5mA, 19mA, 19.5mA, 20mA, etc.

[0060] The coating time directly affects the thickness of the gold film. Plating in the range of 130S to 150S can ensure that the gold film reaches an appropriate thickness. A too thin gold film may not fully cover the surface of the sample, resulting in poor conductivity or blurred images during electron microscope analysis; while a too thick gold film may increase the sample preparation cost and may affect the resolution of the electron microscope. In addition, the choice of coating time also involves the issue of coating efficiency. If the coating time is shorter than 130S, a gold film of sufficient thickness cannot be obtained; and if the coating time is longer than 150S, although a thicker gold film can be obtained, the sample preparation time and cost will be increased. Therefore, plating in the range of 130S to 150S can achieve a good balance between coating efficiency and gold film quality. Exemplarily, the coating time can be 130S, 134S, 138S, 142S, 146S, 150S, etc.

[0061] S5, adhering the bottom surface of the sample after the gold-sprayed conductive treatment to the sample stage, and then connecting the detection surface of the sample to the sample stage, so that the sample and the sample stage become a whole sample;

[0062] The sample after gold spray coating conductive treatment is adhered to the sample stage with double-sided carbon conductive adhesive to ensure the stability and positioning accuracy of the sample during observation. Use double-sided carbon conductive adhesive to connect the detection surface of the sample and the sample stage to ensure good electrical contact and signal transmission. The adhesion and connection between the sample stage and the sample should be firm and reliable to avoid loosening or falling off during observation.

[0063] S6. Use compressed air to blow the entire sample.

[0064] During the sample preparation process, whether through grinding and polishing or other steps, tiny particles, dust or contaminants may be generated on or around the sample surface. If these tiny particles remain on the sample, it will seriously affect the imaging quality of the electron microscope analysis, resulting in blurred images, increased noise and other problems. By blowing and cleaning with compressed air, these tiny particles can be effectively blown away from the surface and surroundings of the sample to ensure the cleanliness of the sample. In addition, during the cleaning process, if physical tools such as brushes and cotton swabs are used for cleaning, it is easy to cause mechanical damage to the sample surface, such as scratches and dents. These damages will not only affect the appearance of the sample, but may also change its microstructure and performance, thereby affecting the results of the electron microscope analysis. Compressed air cleaning and blowing is a non-contact cleaning method that can avoid mechanical damage to the sample surface.

[0065] During the entire sample preparation process, care should be taken to keep samples and tools clean and avoid contamination.

[0066] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples that do not specify specific conditions are usually measured according to industry standards; if there are no corresponding industry standards, they are carried out according to common international standards, conventional conditions, or conditions recommended by the manufacturer.

[0067] Table 1 Sample preparation process parameters of iron oxide scale of steel continuous casting billet for electron microscope analysis

[0068]

[0069] Figure 2 The energy spectrum component analysis results of the interface between the iron oxide scale and the substrate provided in the embodiments of the present application.

[0070] From Table 1 and Figure 2 It can be seen that the sample preparation process parameters of the oxidized iron scale of the steel continuous casting billet used for electron microscope analysis in the embodiment are all within the required range of the present invention, the obtained sample preparation effect is good, the original state of the iron scale is fully and comprehensively displayed, and clear composition detection work can be achieved.

[0071] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0072] 1. This method can clearly show the distribution state of iron oxide scale and its growth law under different conditions during electron microscope analysis, which is of great significance for in-depth understanding of the formation mechanism of iron oxide scale in the continuous casting process of steel and its influence on steel properties.

[0073] 2. This method uses environmentally friendly materials and technologies, such as silver glue, cold mounting materials and gold spraying, which do not produce harmful pollutants and meet the requirements of modern green manufacturing. At the same time, since the high-temperature treatment steps are reduced in the sample preparation process, the dependence on consumables and consumption costs are reduced. The cold mounting and drying steps are relatively simple and quick, which reduces the sample preparation time and improves work efficiency.

[0074] 3. This method is not only suitable for the sample preparation of iron oxide scale of steel continuous casting billets, but can also be widely used in the analysis of other coating samples that require fine sample preparation, showing its wide range of applicability and versatility.

[0075] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.

Claims

1. A method for preparing iron oxide scale of steel continuous casting billet for electron microscope analysis, characterized in that: The method comprises: The steel samples containing easily detached iron oxide scale were treated with silver glue; Using a cold mounting solution, cold mounting the sample after the silver glue treatment, and then drying the sample; Performing grinding and polishing treatment on the dried sample; Conductive treatment of gold coating is performed on the sample after grinding and polishing; Adhere the bottom surface of the sample after the gold-sprayed conductive treatment to the sample stage, and then connect the detection surface of the sample to the sample stage, so that the sample and the sample stage become a whole sample; The entire sample was blown clean with compressed air.

2. The method according to claim 1, characterized in that: The thickness of the silver paste is 1 mm to 2 mm.

3. The method according to claim 1, characterized in that The cold mounting solution comprises epoxy resin and curing agent.

4. The method according to claim 1 or 3, wherein the mass ratio of the epoxy resin to the curing agent is =1:(1.8-2.1).

5. The method according to claim 1, characterized in that The drying is carried out under vacuum.

6. The method according to claim 1 or 5, characterized in that: The drying temperature is 30° C. to 40° C., and the drying time is ≥12 h.

7. The method according to claim 1, characterized in that The grinding and polishing process is a multi-pass polishing process, wherein each polishing process lasts for 15S to 30S.

8. The method according to claim 7, characterized in that In the interval between two adjacent polishing passes of the multi-pass polishing, the polished surface of the sample is subjected to a first air cooling, and the first air cooling time is 8S to 10S.

9. The method according to claim 1, characterized in that: After the grinding and polishing treatment and before the gold spraying and conductive treatment, the sample is subjected to a second air cooling, and the second air cooling time is 5 minutes to 8 minutes.

10. The method according to claim 1, characterized in that The coating current of the gold-spraying conductive coating treatment is 18 mA to 20 mA, and the coating time of the gold-spraying conductive coating treatment is 130S to 150S.

Citation Information

Cited By

  • Metallographic sample for protecting oxidation film and preparation process of metallographic sample

    CN121141282A